Whole rock major, minor, and trace element compositions of basaltic glassy pillow selvages and hyaloclastite from Kverkfjöll, Iceland. ... - Valdimarsdóttir, Iðunn Kara (Zenodo, 2023)
Whole rock compositions of glassy pillow selvages and hyaloclastite (tuff) from the Kverkfjöll region, Iceland, were measured as a part of a master's thesis in geology from the University of Iceland. Major and minor element compositions for the glassy selvages were measured via ICP-OES. Trace element compositions for the glassy selvages and tuff were measured via ICP-MS. Please refer to the actual thesis for more information: Valdimarsdóttir, I. K. (2023). Origin, extent, and emplacement conditions of newly exposed pillow lavas in the Kverkfjöll region, Iceland . [Master's thesis, University of Iceland]. Skemman. ... : {"references": ["Valdimarsd\u00f3ttir, I. K. (2023).\u00a0Origin, extent, and emplacement conditions of newly exposed pillow lavas in the Kverkfj\u00f6ll region, Iceland. [Master's thesis, University of Iceland]. Skemman."]} ...